2021
DOI: 10.1016/j.apsb.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic integration of metal nanoclusters and biomolecules as hybrid systems for therapeutic applications

Abstract: Therapeutic nanoparticles are designed to enhance efficacy, real-time monitoring, targeting accuracy, biocompatibility, biodegradability, safety, and the synergy of diagnosis and treatment of diseases by leveraging the unique physicochemical and biological properties of well-developed bio-nanomaterials. Recently, bio-inspired metal nanoclusters (NCs) consisting of several to roughly dozens of atoms (<2 nm) have attracted increasing research interest, owing to their ultrafine size, tunable fluorescent capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 233 publications
(266 reference statements)
0
17
0
Order By: Relevance
“…[28] While Au I complexes such as auranofin have been extensively researched, recent investigations have shown that gold nanomaterials, including gold nanoclusters (AuNCs), also have potential as antibacterial agents. [29,30] AuNCs are a class of gold nanoparticles that contain up to several hundred Au atoms and are 2 nm or less in diameter. [31,32] Similar to other nanomaterials that possess high specific surface areas, AuNCs can provide multivalent presentation of attached ligands within close proximity, often leading to a marked increase in binding affinity by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…[28] While Au I complexes such as auranofin have been extensively researched, recent investigations have shown that gold nanomaterials, including gold nanoclusters (AuNCs), also have potential as antibacterial agents. [29,30] AuNCs are a class of gold nanoparticles that contain up to several hundred Au atoms and are 2 nm or less in diameter. [31,32] Similar to other nanomaterials that possess high specific surface areas, AuNCs can provide multivalent presentation of attached ligands within close proximity, often leading to a marked increase in binding affinity by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the emitted light has a longer wavelength, and therefore lower energy, than the absorbed radiation. However, when the absorbed electromagnetic radiation is intense, it is possible for one molecule to absorb two photons; this two-photon absorption may lead to the emission of radiation with a shorter wavelength than the absorbed radiation [ 22 ]. Fluorescence imaging has evolved into a novel and promising tool for in vivo imaging, as it can achieve real-time sub-cellular resolution imaging, and hence be widely used in the field of biological and medical detection and treatment.…”
Section: Potential Modes Of Copper Nanocluster Usage In Bioimagingmentioning
confidence: 99%
“…To the best of our knowledge, this article is the first to analyze and summarize such phenomena. This article pays great attention to the interface modulation of nucleic acids to nanozymes: modification, binding, immobilization, and the resulting major changes in interface components in the structure of nanozymes, which lead to an increase or decrease in enzyme catalytic activity [46][47][48][49][50]. The controllability and accuracy of modulation technology is an important force for promoting the progress of social civilization.…”
Section: Nucleic Acid Modulation For Functional Nanozymementioning
confidence: 99%